2010
DOI: 10.1021/ja105183w
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer−Oxygen Transfer Oxygenation of Sulfides Catalyzed by the H5PV2Mo10O40 Polyoxometalate

Abstract: The oxygenation of sulfides to the corresponding sulfoxides catalyzed by H(5)PV(2)Mo(10)O(40) and other acidic vanadomolybdates has been shown to proceed by a low-temperature electron transfer-oxygen transfer (ET-OT) mechanism. First, a sulfide reacts with H(5)PV(2)Mo(10)O(40) to yield a cation radical-reduced polyoxometalate ion pair, R(2)(+*),H(5)PV(IV)V(V)Mo(10)O(40), that was identified by UV-vis spectroscopy (absorptions at 650 and 887 nm for PhSMe(+*) and H(5)PV(IV)V(V)Mo(10)O(40)) and EPR spectroscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 20 publications
4
67
0
Order By: Relevance
“…The special behaviour of the aldehydic C2-substrates in the reaction system presented here becomes more understandable taking into account literature reports on radical reaction pathways of aldehydes in POM catalyzed oxidation systems using molecular oxygen. 28 Using the C2-substrates we proved that at least for the substrates that contain an aldehyde function there is not only one mechanism involved. Only a superposition of at least two reaction mechanisms can explain the product mixture obtained from the aldehydic C2-substrates.…”
Section: Resultsmentioning
confidence: 89%
“…The special behaviour of the aldehydic C2-substrates in the reaction system presented here becomes more understandable taking into account literature reports on radical reaction pathways of aldehydes in POM catalyzed oxidation systems using molecular oxygen. 28 Using the C2-substrates we proved that at least for the substrates that contain an aldehyde function there is not only one mechanism involved. Only a superposition of at least two reaction mechanisms can explain the product mixture obtained from the aldehydic C2-substrates.…”
Section: Resultsmentioning
confidence: 89%
“…POMs have stimulated many current research activities in a broad range of the oxidation process because their reactivity and acidities can be finely tuned by choosing the constituent elements and counter cations. For example, in the common Keggin structure, [X n+ W 12 O 40 ] (8Àn)À , the central hetero atom, X n+ , can be a list of elements in the periodic 28 In this process, an outer-sphere ET reaction between R 2 S and H 5 PV 2 MO 10 O 40 leads to an ion pair (step (a) in Scheme 17), followed by an OT reaction that removes VO 2+ from POMs. The sulfoxide is finally liberated with the formation of the reduced H 7 PV IV 2 Mo 10 O 40 (step (c)).…”
Section: Oxidative Reactivity Of Polyoxometalatesmentioning
confidence: 99%
“…[7] As part of our studies on electron transfer oxidations catalyzed by the H 5 catalyzes the electron transfer transfer-oxygen transfer oxidation of sulfides, RSR' (R, R' = aryl, alkyl), to yield sulfoxides, RS(O)R'. [9] The reactions take place by initial formation of a cation radical, RSR'+C, and a reduced polyoxometalate, H 5 Interestingly, we observed that heteroaromatic sulfides, that is, thiophene derivatives, were not oxygenated, presumably due to their stability. We now report that such heteroaromatic thiophenes, such as benzothiophene (BT), dibenzothiophene (DBT) and 4,6-dimethyldibenzothiophene (DMDBT), can be oxidatively polymerized by H 5 PV V 2 Mo 10 O 40 supported on an inert matrix such as silica.…”
mentioning
confidence: 74%
“…Thus, a reaction pathway can be assumed in which H 5 PV 2 Mo 10 O 40 can activate benzothiophene by electron transfer to yield a benzothiophene cation radical (Scheme 2). [9] The benzothiophene cation radical is predicted to be an electrophile, and therefore in the presence of excess benzothiophene can initiate an electrophilic aromatic substitution reaction which is facilitated by the electron-donating property of the thiophene substituent. The electrophilic substitution can be followed by the known H 5 PV 2 Mo 10 O 40 -catalyzed aromatization reaction; [10] and reoxida- catalyst can be recycled by pyrolysis of the solid under wet oxygen at 300-350 8C for 12 h. The activity of the catalyst is retained over the five cycles tested and appeared to be stable, judging from IR spectroscopy.…”
mentioning
confidence: 99%